PELATIHAN FOTOGRAFI PRODUK MENGGUNAKAN SMARTPHONE UNTUK MENINGKATKAN VISUAL BRANDING PADA UMKM KERAJINAN TANDUK SAPI DESA PUCANG, MAGELANG - Setya Indah Isnawati; Ari Eko Budiyanto; Ahmad Ali (ABDI MAKARTI, 2022)
Product photos with smartphones can be a solution for MSMEs in facing the risk of access to the market. Smartphones are now equipped with cameras and photo editing applications that are very adequate and easy to create visual branding. One of the product photos used in the Community Service (PkM) training this time is product photography. The partner of this PkM is "Toko Subur", which is a horn and souvenir handicraft business which is located in Pucang Village, Secang, Magelang. The problem raised is the limitation of soft skills in applying smartphones for product photography purposes. For this reason, the PkM Team provides a solution in the form of simple product photography training using a smartphone and other supporting properties. The method used is direct training using a smartphone or simple property for SMEs "Toko Subur" as well as joint discussions regarding the obstacles they face. The output of this PkM is the formation of soft skills for MSME actors in the field of product photography to create visual branding so that they are able to attract potential consumers and increase sales from both social media and e-commerce.